Non-adenosine Nucleoside Inosine, Guanosine and Uridine as Promising Antiepileptic Drugs: a Summary of Current Literature - Kovacs, Zsolt; A. Kekesi, Katalin; Juhasz, Gabor; Barna, Janos; Heja, Laszlo; Lakatos, Renata; Dobolyi, Arpad (Mini Reviews in Medicinal Chemistry, 2014)
Adenosine (Ado) and some non-adenosine (non-Ado) nucleosides including inosine (Ino), guanosine (Guo) and uridine (Urd) are modulatory molecules in the central nervous system (CNS), regulating different physiological and pathophysiological processes in the brain such as sleep and epilepsy. Indeed, different drugs effective on adenosinergic system (e.g., Ado metabolism inhibitors, agonists and antagonists of Ado receptors) are being used in drug development for the treatment of epileptic disorders. Although (i) endogenous Ino, Guo and Urd showed anticonvulsant/antiepileptic effects (e.g., in quinolinic acid - induced seizures and in different epilepsy models such as hippocampal kindling models), and (ii) there is a need to generate new and more effective antiepileptic drugs for the treatment of drug-resistant epilepsies, our knowledge about antiepileptic influence of non-Ado nucleosides is far from complete. Thus, in this review article, we give a short summary of anticonvulsant/antiepileptic effects and mechanisms evoked by Ino, Guo, and Urd. Finally, we discuss some non-Ado nucleoside derivatives and their structures, which may be candidates as potential antiepileptic agents.
Keywords: uridine